(untitled) - Demko, George J. (New York, 1992)
Geographical illiteracy is shockingly pervasive. In this major now book, author George Demko, former Director of the Office of the Geographer of the U.S., unravels the mysteries of Geography and tells us what "New Geography" is--what is where, why it's there and why we need to know or care.
Keywords: Địa lý,Geography